2011
DOI: 10.1128/aem.00067-11
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Borrelia burgdorferi Sensu Lato Prevalence in Questing Ixodes ricinus Ticks with Specific Abiotic Traits in the Western Palearctic

Abstract: This meta-analysis of reports examining ticks throughout the Western Palearctic region indicates a distinct geographic pattern for Borrelia burgdorferi sensu lato prevalence in questing nymphal Ixodes ricinus ticks. The greatest prevalence was reported between the 5°E and 25°E longitudes based on an analysis of 123 collection points with 37,940 nymphal tick specimens (87.43% of total nymphs; 56.35% of total ticks in the set of reports over the target area). Climatic traits, such as temperature and vegetation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
68
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 33 publications
5
68
1
Order By: Relevance
“…Such a phenomenon was also observed by Petko et al (19), Wójcik-Fatla et al (28) and Nazzi et al (27). Similarly to 2006, in the presented study, it was confirmed that B. burgdorferi s.s. (26) was the dominant genospecies within B. burgdorferi s.l., whereas in most other reports from Central Europe, Borrelia afzelii and Borrelia garinii (2,7,13,24) are the genospecies which occur most frequently.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such a phenomenon was also observed by Petko et al (19), Wójcik-Fatla et al (28) and Nazzi et al (27). Similarly to 2006, in the presented study, it was confirmed that B. burgdorferi s.s. (26) was the dominant genospecies within B. burgdorferi s.l., whereas in most other reports from Central Europe, Borrelia afzelii and Borrelia garinii (2,7,13,24) are the genospecies which occur most frequently.…”
Section: Discussionmentioning
confidence: 94%
“…However, some authors, such as Boyard et al (23) and Estrada-Pena et al (24), indicate that the risk of exposure to Borrelia-infected ticks depends on the properties of the forest environment, such as: the composition of tree species, undergrowth, fragmentation, microclimate. These environmental conditions vary to a great extent between climate zones and countries and depend on forest managements.…”
Section: Discussionmentioning
confidence: 99%
“…and its genospecies in Europe (see reviews by Hubálek and Halouzka, 1998;Rauter and Hartung, 2005). Considered individually, these data have local epidemiological importance, but retrospective modeling and metaanalysis of prevalence data resulted in valuable information on the importance of associated biotic and abiotic factors (Rauter and Hartung, 2005;Estrada-Peña et al, 2011). Although Romania is a relatively large country (ranked 13/54 in Europe in total area), with a high tick population density and available host diversity (Mihalca et al, 2012a), it has been poorly investigated from this point of view.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the prevalence of tick-borne pathogens such as Borrelia burgdorferi and Anaplasma phagocytophilum has been correlated with seasonal climatic changes (14). Therefore, it is expected that other microbial tenants within tick hosts are affected in the same manner.…”
mentioning
confidence: 99%